Effect of microbial transglutaminase-induced crosslinking on rheological properties of gelatin methacryloyl ink for 3D printing - Zhou, Miaomiao (2018)
3D bioprinting provides an efficient mean to fabricate 3D cellular constructs with defined shape and controlled spatial organization. Despite some remarkable successes, it still remains challenging to develop a bioink to meet the requirements (cell-compatibility, printability, structural stability post printing) for printing. Herein, this thesis presents a new strategy for bioprinting of photo crosslinkable Gelatin methacryloyl (GelMA) through enzymatic crosslinking reactions. Ca2+-independent microbial transglutaminase (MTGase) catalyzed covalent bond formation between chains of GelMA and rheological properties were first optimized. A secondary post-printing crosslinking step (photo crosslinking) was then introduced to ensure long term stability of the printed structure for subsequent cell studies. Cells encapsulated in the printed structure were viable for at least 7 days indicating excellent biocompatibility. This strategy for printing of cell-laden photo crosslinkable GelMA may find valuable application in organ printing and tissue engineering.